PRODUKSI DAN DAYA TERIMA CHEESE SPREAD ANALOGUE BERBAHAN BAKU SOFT TOFU DAN PAPRIKA POWDER (Jurnal Fakultas Teknik Kuningan, 2022)
Soybean is an important raw material in meeting the nutritional needs of the community which has a fairly high content of vegetable protein at a relatively low price. Soybean seed protein content of approximately 35%, 15% fat and minerals. Based on data from the Ministry of Industry in 2015, the average soybean consumption per person in Indonesia has increased, in 2010 it was 907,031 tons/year, in 2014 it was 954,997 tons/year. 2015 as many as 963,183 tons/year.The purpose of this study was to determine the acceptability of the cheese spread analogue using Design Expert version 10.0, the d-optimal method based on the response of color, aroma, taste and spreadability. The results of the study of the selected cheese spread analogue, namely formula 2 with a percentage of 35% soft tofu raw materials and 5% paprika powder, the acceptability was tested by 15 expert panelists with a response to color, aroma, taste and spreadability.